The Functions of Bursal Hexapeptide (BHP) on Immune Response and the Molecular Mechanism on Immature B Cell - Zong, Man M.; Zhou, Guang Fang; Zheng, Yang; Yu, Yuan Nan; Zhou, Chuan Jie; Feng, Xiu Li; Cao, Rui Bing; Chen, Pu Yan; Yang, Mei (Protein and Peptide Letters, 2017)
Background: The bursa of Fabricius (BF) is an acknowledged central immune organ, and is important to B cell differentiation. Bursal hexapeptide (BHP) is the recently reported bursalderived peptide, while its inducing function on immune response is uncertain. Objectives: The main objective of this study was to analyze the immune responses to JEV vaccine in mice induced by BHP plus JEV vaccine, and to detect the signal and biological functions of BHP on immature B cells. Methods: Mice were immunized with Japanese encephalitis virus (JEV) vaccine and BHP from 0.01 mg/mL to 0.25 mg/mL to detect antibody response and cellular immune response, respectively. The production of IgG, IgG1 and IgG2a specific to JEV in serum from immunized mice were measured by ELISA, and T cell subpopulation from immunized mice were detected with using fluorochrome conjugated mAbs of the corresponding PE-Cys/FITC/PE by flow cytometry. Spleen cells from all immunized mice were harvested after one week of second immunization for lymphocyte proliferation assay. Mouse immature B cell WEHI-231 cell was treated with 0.01μg/mL BHP for 4h, and analyzed the involved biological function and pathway of differentially expressed genes with gene microarray. Results: BHP co-immunization with JEV vaccine generated significant increased antibody levels, neutralizing antibody titers and spleen lymphocyte viability, compared to that of vaccine control. The subpopulations of T cells in spleen lymphocytes were significantly modified in the mice coimmunized with JEV vaccine and BHP. The analysis results of gene expression profiles of WEHI- 231 mouse immature B cells with BHP treatment showed that the regulated genes with BHP treatment were involved various immune related biological functions, including proliferation and activation of lymphocyte and T cell, T cell mediated immunity and regulation of adaptive immune response. Furthermore, BHP stimulated three significant enriched pathways, including amphetamine addiction, long-term potentiation, and RIG-I-like receptor signaling pathway. Conclusion: Our results indicated BHP induced significant humoral and cellular immunity to JEV vaccine, and regulated various biological processes and signalling related to immune activation in immature B cells. These results proposed the immunomodulatory function and mechanism of BHP on immune induction, which provided the novel insight on the candidate reagent for immune improvement.
Keywords: T cell subtype